Remote Sensing and GIS Technologies for Monitoring and Prediction of Disasters - Nayak, Shailesh.; Nayak, Shailesh.; Zlatanova, Sisi.; Zlatanova, Sisi. (Environmental Science,, 2008)
Lessons learned in the last several years have given clear indications that the prediction and efficient monitoring of disasters is one of the critical factors in decision-making process. In this respect space-based technologies have the great potential of supplying information in near real time. Earth observation satellites have already demonstrated their flexibility in providing data to a wide range of applications: weather forecasting, person and vehicle tracking, alerting to disaster, forest fire and flood monitoring, oil spills, spread of desertification, monitoring of crop and forestry damages. This book focuses on a wider utilisation of remote sensing in disaster management. The discussed aspects comprise data access/delivery to the users, information extraction and analysis, management of data and its integration with other data sources (airborne and terrestrial imagery, GIS data, etc.), data standardization, organisational and legal aspects of sharing remote sensing information.